Revealing an outward-facing open conformational state in a CLC Cl(–)/H(+) exchange transporter - Khantwal, Chandra M (eLife, 2016)
CLC secondary active transporters exchange Cl(-) for H(+). Crystal structures have suggested that the conformational change from occluded to outward-facing states is unusually simple, involving only the rotation of a conserved glutamate (Glu(ex)) upon its protonation. Using (19)F NMR, we show that as [H(+)] is increased to protonate Glu(ex) and enrich the outward-facing state, a residue ~20 Å away from Glu(ex), near the subunit interface, moves from buried to solvent-exposed. Consistent with functional relevance of this motion, constriction via inter-subunit cross-linking reduces transport. Molecular dynamics simulations indicate that the cross-link dampens extracellular gate-opening motions. In support of this model, mutations that decrease steric contact between Helix N (part of the extracellular gate) and Helix P (at the subunit interface) remove the inhibitory effect of the cross-link. Together, these results demonstrate the formation of a previously uncharacterized 'outward-facing open' state, and highlight the relevance of global structural changes in CLC function. DOI: http://dx.doi.org/10.7554/eLife.11189.001